TÜRK İŞ HUKUKUNDA REKABET YASAĞI SÖZLEŞMESİ - (:unkn) unknown (My University, 2017)
İş sözleşmesinden doğan sadakat borcunun bir gereği olan rekabet etmeme borcu, iş sözleşmesinin bitimi ile sona erer. İş sözleşmesinin sona ermesinden sonraki dönemde işçiye karşı rekabet etmeme borcunun ileri sürülebilmesi için ise, rekabet yasağının iş sözleşmesinde ayrıca öngörülmesi veya iş sözleşmesinden ayrı ve özel bir rekabet yasağı sözleşmesiyle düzenlenmiş olması gerekir. Rekabet yasağı sözleşmesine ilişkin düzenlemelere, 6098 sayılı Türk Borçlar Kanunu'nun 444 ila 447. maddelerinde yer verilmiştir.

Non - competition obligation, as an integral part of the duty of fidelity residing in the employment contracts, dose not extend after termination of the contract of employment. Assertion of the non - competition obligation to the employee after the termination of the employment contract requires either a non - competition clause, which is stipulated on the contract of employment; or a separate and single noncompetition contract. Relevant regulations regarding to non - compete agreements can be found between the articles 444- 447 of the Turkish Code of Obligations numbered 6098.
Noncompetition Contract In Turkish Labour Law
Keywords: Hukuk